Pengabdian Masyarakat: Edukasi dan Skrining Hemoglobin-Hematokrit sebagai Deteksi Dini Anemia pada Usia Produktif - Herdiman, Julia; Santoso, Alexander Halim; Gunaidi, Farell Christian; Setia, Nicholas; Rayhan, Naufal (Jurnal Pengabdian West Science, 2025)
Anemia is a health condition characterized by low hemoglobin or hematocrit levels, which affects the blood's ability to carry oxygen, resulting in a decrease in quality of life. This condition is common in the productive and elderly population, and has the potential to cause physical and cognitive disorders. This Community Service Activity aims to conduct early detection of anemia in the adult population in Sunter, North Jakarta through screening of hemoglobin and hematocrit levels using the Plan-Do-Check-Action (PDCA) method. Hemoglobin and hematocrit measurements were carried out using the Point of Care Testing (POCT) tool. The results showed that 5 men (22.73%) and 17 women (77.27%) had hemoglobin levels below normal. Increasing public awareness of adequate nutritional intake and healthy eating patterns, especially those rich in iron and vitamin B12, can prevent anemia. Early detection of anemia is very important to identify individuals at risk, so that timely intervention can be given. This is expected to reduce the prevalence of anemia and improve the quality of life of the community